FLIGHT TESTING IS OUR PROFESSION – AN OVERVIEW OF TEST FLIGHT AND DEVELOPMENT CENTRE - Schuite, Gerard (International Foundation for Telemetering, 1999)
International Telemetering Conference Proceedings / October 25-28, 1999 / Riviera Hotel and Convention Center, Las Vegas, Nevada === The aim of this presentation is to give an overview of TFDC’s capabilities as a flight test centre and the approach with respect to the management of flight testing.